Challenge in diagnosis and management of lentigo maligna and lentigo maligna melanoma - Anggraini, Ika; Miranda, Elisa; Wibawa, Larisa Paramitha; Krisanti, Roro Inge Ade; Sampurna, Adhimukti T (UI Scholars Hub, 2017)
Lentigo maligna (LM) is a subtype of melanoma in situ, which can evolve into lentigo maligna melanoma (LMM) if treated inadequately. LM and LMM are usually found on chronically sun damaged skin such as the face (cheek and nose) of the elderly on seventh or eight decades. Clinical manifestation of LM may be quite subtle, so early diagnosis is difficult to perform.The treatment of LM and LMM are challenging due to ill-defined clinical margin, predilection on the face with great size, and preponderance of the elderly, which are potential for recurrency and progressiveness from LM into LMM.